The summer book eaudiobook - Jansson, Tove (Tantor Media, 2022)
In The Summer Book Tove Jansson distills the essence of the summer—its sunlight and storms—into twenty-two crystalline vignettes. This brief novel tells the story of Sophia, a six-year-old girl awakening to existence, and Sophia's grandmother, nearing the end of hers, as they spend the summer on a tiny unspoiled island in the Gulf of Finland. The grandmother is unsentimental and wise, if a little cranky; Sophia is impetuous and volatile, but she tends to her grandmother with the care of a new parent. Together they amble over coastline and forest in easy companionship, build boats from bark, create a miniature Venice, write a fanciful study of local bugs. They discuss things that matter to young and old alike: life, death, the nature of God, and of love. "On an island," thinks the grandmother, "everything is complete." In The Summer Book , Jansson creates her own complete world, full of the varied joys and sorrows of life.